Manufacturing SMEs Competitiveness against the Crisis: Management Characteristics and New Perspectives - Nikolaos Sariannidis; Christos Lemonakis; Alexandros Garefalakis; Tzallas Paraskevas (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to study the drivers of competitiveness in sectors of the Greek manufacturing industry, both in the pro and post economic crisis era, based on firm level financial and qualitative data cover this gap, providing evidence about factors impact competitive dynamic of Greek manufacturing SMEs taking into account aspects of IT, knowledge management, training, innovation and financial ratios. The study is structured as follows: the next section presents a literature review on this subject, while section 3 highlight the methodology as well as the model approach of the study. In section 4, the empirical results of the study are presented and section 5 the main findings are discussed. Section 6 summarizes the empirical findings and draws the policy implications of the study.